2003
DOI: 10.1038/nrc1186
|View full text |Cite
|
Sign up to set email alerts
|

The role of Notch in tumorigenesis: oncogene or tumour suppressor?

Abstract: Notch signalling participates in the development of multicellular organisms by maintaining the self-renewal potential of some tissues and inducing the differentiation of others. Involvement of Notch in cancer was first highlighted in human T-cell leukaemia, fuelling the notion that aberrant Notch signalling promotes tumorigenesis. However, there is mounting evidence that Notch signalling is not exclusively oncogenic. It can instead function as a tumour suppressor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
558
0
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(587 citation statements)
references
References 132 publications
19
558
0
10
Order By: Relevance
“…However, it should be noted that Notch signaling can be both oncogenic and tumor suppressive even in a single-cell type (Radtke and Raj, 2003;Leong and Karsan, 2006). In fact, one study, which found that the Notch pathway is involved in melanoma progression, presented findings that conflicted with our own (Hoek et al, 2004).…”
Section: Discussionmentioning
confidence: 69%
“…However, it should be noted that Notch signaling can be both oncogenic and tumor suppressive even in a single-cell type (Radtke and Raj, 2003;Leong and Karsan, 2006). In fact, one study, which found that the Notch pathway is involved in melanoma progression, presented findings that conflicted with our own (Hoek et al, 2004).…”
Section: Discussionmentioning
confidence: 69%
“…Recently, we demonstrated that Notch, which is an evolutionally conserved molecule that controls cell fate decision in a variety of cells [27,28], drives IL-22 secretion by stimulating the AHR [29]. Mice that are deficient in RBP-J, a key mediator of Notch signaling, are highly susceptible to the detrimental immunopathology associated with Con A-induced hepatitis with little IL-22 production [29].…”
Section: Introductionmentioning
confidence: 99%
“…In infection with an attenuated strain of Salmonella enterica serovar Enteritidis, p19-deficient mice showed reduced survival and exacerbated liver necrosis only in the absence of IL-12 in an IL-17-independent manner [10]. In peroral infection with Toxoplasma gondii, which leads to the development of small intestine inflammation, the IL-23-dependent upregulation of IL-22 is essential for the development of ileitis; on the other hand, IL-17 is downregulated and dispensable [11].IL-22 is a member of the IL-10 cytokine family and plays important roles in inflammation, immune surveillance and tissue homeostasis [12][13][14][15] [10,25,26].Recently, we demonstrated that Notch, which is an evolutionally conserved molecule that controls cell fate decision in a variety of cells [27,28], drives IL-22 secretion by stimulating the AHR [29]. Mice that are deficient in RBP-J, a key mediator of Notch signaling, are highly susceptible to the detrimental immunopathology associated with Con A-induced hepatitis with little IL-22 production [29].…”
mentioning
confidence: 99%
“…1), Notch (REF. 2), the Runt-related transcription factors (Runx) 3 , E2f (REF. 4) and CDKN1A (cyclin-dependent kinase inhibitor 1A, the gene that encodes p21) 5 .…”
mentioning
confidence: 99%